Análise da resistência à compressão e consistência de concreto produzido com brita calcária e aditivo plastificante - Paiva Filho, Julio Cesar de (Universidade Federal Rural do Semi-Árido, 2017)
According to IBRAM - Mining Brazilian Institute, the western region of Rio Grande of Norte presents an enormous amount of limestone deposits, an essential raw material for the manufacture of cement, one of the most used materials in civil construction. The great amount of limestone provided the installation of cement industries, which use the rock suitable for cement manufacturing and reject what has not been used. This limestone tailings can be used for the production of concrete. The limestone rock presents a large amount of fine particles and a high water absorption, which results in a high water / cement factor for a suitable workability, causing loss of the mechanical properties of the concrete. Therefore, due to the need for proper disposal of the limestone rock waste and with the purpose of assigning economic value to the aggregate of this rock, the objective was to find a workable and compressive resistant trait for concretes, where limestone was benefited through sieving in the 4.75mm mesh sieve to reduce the fine particle content and the use of a sulphonated salts based plasticizer additive to reduce the water / cement content, according to the limits presented in ABNT NBR 6118/2014. In the study, large aggregate characterization tests were performed according to ABNT NBR 7211/2009. The behavior of the concrete was determined by fixing the water / cement factor and the percentage of additive, but varying from one reference trait (1.0, 2.5, 2.5, 0.6, 4.5%), if the quantity of aggregates. For all of the traits studied, the Slump Test was performed to determine its consistency in the fresh state and resistance to axial compression at 28 days in the hardened state. Through the study it was observed that high amounts of plasticizing additive reduce the time of picking of the concrete, it is not possible to demold them with 24h after molding. Even when the amount of aggregates was varied, for a high water / cement factor and plasticizer additive, the traces of calcareous concrete studied did not present adequate compression strength to be used as structural concrete.
Monografia
Keywords: Concreto; Brita Calcária; Aditivo; Trabalhabilidade e resistência; Concrete; Limestone rock; Additive; Workability and Resistance; ENGENHARIAS::ENGENHARIA CIVIL